Cultural heritage, ethics and the military - Stone, Peter 1957- (Heritage matters series, 2011)
Examines the ethical dilemma of whether, and how, archaeologists and other experts should work with the military to protect cultural property in times of conflict. The world reacted with horror to the images of the looting of the National Museum in Iraq in 2003 - closely followed by other museums and then, largely unchecked, or archaeological sites across the country. This outcome had been predicted by many archaeologists, with some offering to work directly with the military to identify museums and sites to be avoided and protected. However, this work has since been heavily criticised by others working in the field,who claim that such collaboration lended a legitimacy to the invasion. It has therefore served to focus on the broader issue of whether archaeologists and other cultural heritage experts should ever work with the military,and, if so, under what guidelines and strictures.